2019
DOI: 10.2196/12252
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Smoking Cessation Smartphone App Integrated With a Mobile Carbon Monoxide Checker for Smoking Cessation Treatment: Protocol for a Randomized Controlled Trial

Abstract: Background Smoking cessation treatment programs have been widely available for patients with nicotine dependence. Despite intensive programs, the continuous abstinence rate (CAR) from weeks 9-12 is still about 50%. Recently, a smartphone app emerged as a novel tool for therapeutic interventions, including nicotine dependence. In this study, we developed “CureApp Smoking Cessation” (CASC), which consists of a smartphone app for patients and a Web-based patient management software for doctors with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…2). A detailed study protocol was presented elsewhere 28 . Briefly, participants were recruited from 31 smoking cessation clinics in Japan, from October 2017 to January 2018, and allocated 1:1 to the CASC intervention group and the control group.…”
Section: Methodsmentioning
confidence: 99%
“…2). A detailed study protocol was presented elsewhere 28 . Briefly, participants were recruited from 31 smoking cessation clinics in Japan, from October 2017 to January 2018, and allocated 1:1 to the CASC intervention group and the control group.…”
Section: Methodsmentioning
confidence: 99%
“…A previous single arm, prospective pilot study showed that the CASC, in addition to the standard program, led to significantly higher CAR from weeks 9 to 24 when compared with a historical control group [21]. Currently, there is an ongoing Phase III randomized controlled clinical trial to evaluate the efficacy of the CASC [20]. The standard smoking cessation program in Japan requires that patients’ exhaled CO concentration be measured at each clinic visit [5], and the information on their CO level is helpful for the primary doctor to give treatment advice on each visit.…”
Section: Discussionmentioning
confidence: 99%
“…The CASC consists of the following: (1) a CASC smartphone app for patients with nicotine dependence, (2) a mobile CO checker for patients, and (3) a Web-based patient management software for health care providers [20]. Participants are asked to watch a 5- to 10-min lecture on smoking cessation every day (see Multimedia Appendix 3 for the specifics).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As information and communication technology (ICT) become increasingly central to our daily lives, development of digital health care and medicine has become a “hot” topic 9,10 . In the era of digital therapeutics (DTx), various trials using applications for chronic conditions such as nicotine dependence, 11,12 substance abuse, 13 or attention deficit hyperactivity disorder 14 have been initiated. In the case of hypertension management, several non‐pharmacological intermittent educational interventions have been well‐validated in previous studies.…”
Section: Introductionmentioning
confidence: 99%